Audit Tata Kelola Sistem Informasi Menggunakan Framework COBIT 5 Studi Kasus Pada LPD Desa Temesi - Pande Nyoman Adi Putra; Ni Made Estiyanti; I Gede Juliana Eka Putra (Prosiding, 2022)
The LPD Desa Temesi is one of the village credit institutions that aims to provide decent financial services for village manners (customers), encourage the development of UMKM in Pakraman village manners, and create technology-based and targeted innovations. To realize this goal, the LPD Desa Temesi must be able to adapt information technology to the times. This study aims to find out how governance on a desktop-based system has been implemented by LPD Desa Temesi and to know the maturity level of IT governance so that it can provide recommendations in improving IT governance. This research method was carried out qualitatively and quantitatively. Data was collected by means of interviews, questionnaires and documentation studies. The data obtained will be analyzed by ISO/IEC 15504 from IT governance, so that the level of capability of IT governance can be known. Based on the results of the analysis, the average capability level in the domains EDM04, APO01, APO06, APO07, APO12, BAI09, DSS03, MEA01 is established and the level of maturity expected by LPD Desa Temesi is at level 4 (predictable) so that the results can be used as a reference in improvement of IT governance processes in the LPD Desa Temesi